Formation and evolution of a 0.242 M⊙ solar masses helium white dwarfs in presence of element diffusion - Althaus, Leandro Gabriel (2001)
Conventional wisdom indicates that a millisecond pulsar is recycled during the mass transfer stage in a binary system. Usually, the companion to the pulsar is a low-mass white dwarf. If zero ages are set at the end of mass transfer, the ages of both objects should be the same. Available models characterized by dominant hydrogen burning lead to a strong discrepancy between the ages of PSR B1855]09 and its white dwarf companion. We interpret such a discrepancy as a direct consequence of ignoring element di usion in the stellar models. We show that in the frame of models in which di usion is properly accounted for, ages naturally come into a nice agreement. Consequently, we do not have to invoke any ad hoc mass loss or exotic mechanisms to account for the ages of the stars that belong to the binary system PSR B1855]09.